2013
DOI: 10.1007/s13205-013-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid purity assessment in Eucalyptus F1 hybrids using microsatellite markers

Abstract: The worldwide expansion of hybrid breeding and clonal forestry is to meet the demands of paper pulp and bioenergy. Although India was one of the pioneers in hybrid production of eucalypts only recently the hybrid clonal forestry is gaining momentum. Inter-specific hybrids are being produced to exploit the hybrid vigor of F1 individuals. Quality control genotyping for hybrid purity and parentage confirmation at the early stage is one of the essential criteria for clonal propagation and field trails for the asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…Hybrid purity tests is crucial in crop hybridization as the genetic purity of the F 1 seeds during the cross between the parental lines could be affected by foreign or self pollen (Subashini et al 2014). Non-essential genotypes called false hybrids should be removed at an early step of the amelioration strategy (Subashini et al 2014).…”
Section: Fingerprinting Of Hybrids and Their Parental Lines And Hybrimentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid purity tests is crucial in crop hybridization as the genetic purity of the F 1 seeds during the cross between the parental lines could be affected by foreign or self pollen (Subashini et al 2014). Non-essential genotypes called false hybrids should be removed at an early step of the amelioration strategy (Subashini et al 2014).…”
Section: Fingerprinting Of Hybrids and Their Parental Lines And Hybrimentioning
confidence: 99%
“…Hybrid purity tests is crucial in crop hybridization as the genetic purity of the F 1 seeds during the cross between the parental lines could be affected by foreign or self pollen (Subashini et al 2014). Non-essential genotypes called false hybrids should be removed at an early step of the amelioration strategy (Subashini et al 2014). Hybrid purity tests are also required where true hybrids are needed to develop genetic linkage maps, QTL research and marker assisted selection (Subashini et al 2014).…”
Section: Fingerprinting Of Hybrids and Their Parental Lines And Hybrimentioning
confidence: 99%
See 1 more Smart Citation
“…Such hybrids were essential to map genes controlling various economically important traits. Molecular markers based hybrid purity tests have been used in many crop species such as rice (Yashitola et al, 2002;Sundaram et al, 2008;Tamilkumar et al, 2009, Bora et al, 2016), maize (Asif et al, 2006Salgado et al, 2006), cotton (Selvakumar et al, 2010) and safflower (Naresh et al, 2009), Eucalyptus (Subashini et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed a high genetic diversity in both species, but care should be taken in avoiding related trees, particularly in the case of I. ingoides. We advise that future studies on hybridization and introgression in both species should be done together with flooding tolerance ability and legume and yield in hybrids testing, and wild hybrids could be procured by making use of today's available approaches, e.g., with tools developed specially for this genus by Dexter et al (2010), which include both morphological and molecular approaches, and by Subashini et al (2014) and Larcombe et al (2014) in Eucalyptus. Also, vegetative propagation could be used to propagate hybrids, since Inga species can be propagated easily from semi-ripe branch cuttings, and, for example, I. edulis is considered an easy-to-root species (Pennington 1998).…”
Section: Suitability Of a Hybridization Programmentioning
confidence: 99%